2015
DOI: 10.1152/physiol.00025.2014
|View full text |Cite
|
Sign up to set email alerts
|

NOD-Like Receptors: Guardians of Intestinal Mucosal Barriers

Abstract: The NOD-like receptors (NLRs) are cytosolic pattern-recognition receptors, which are critically involved in mucosal immune defense. The association of the NLR, NOD2, with inflammatory bowel disease first pointed to the NLRs potential function as guardians of the intestinal barrier. Since then, several studies have emphasized the importance of NLRs in maintaining gut homeostasis and intestinal infections, and in shaping the microbiota. In this review, we will highlight the function of NLRs in intestinal inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 120 publications
(127 reference statements)
2
34
0
5
Order By: Relevance
“…Gut microbes impact local and systemic inflammation through pattern recognition receptors (PRRs) [147, 148]. Accumulating evidence has revealed that gut microbes may regulate fat mass expansion via their fermentative products and mediate the suppression of the fasting induced adipose factor [69, 149152].…”
Section: Reviewmentioning
confidence: 99%
“…Gut microbes impact local and systemic inflammation through pattern recognition receptors (PRRs) [147, 148]. Accumulating evidence has revealed that gut microbes may regulate fat mass expansion via their fermentative products and mediate the suppression of the fasting induced adipose factor [69, 149152].…”
Section: Reviewmentioning
confidence: 99%
“…Pattern recognition receptors (PRRs) are innate immune components, which mainly involves Toll-like receptors (TLRs) and nucleotide oligomerization domain (NOD)-like receptors (NLRs). PRRs are expressed in intestinal epithelial cells [11,12] and are able to recognize microbial-associated molecular patterns (MAMPs) to develop either inflammatory or tolerance responses [13]. In this context, several studies have reported that numerous PRRs, as TLR2, TLR4 [14] and NOD2 [15], seem to be implicated in IBD due to the dysfunctional recognition of commensal microbiota [16].…”
Section: Introductionmentioning
confidence: 99%
“…NOD2 plays a key role in intestinal homeostasis, developing a tolerance response to the commensal microbiota and protecting the host against pathogenic microorganisms through pro-inflammatory intracellular pathways, such as NF-κB [11].…”
Section: Introductionmentioning
confidence: 99%
“…TLRs and NLRs recognize common motifs present in bacteria and viruses with some specificities and complementarities allowing the detection, sampling and coordinated response to microbiological insults. NOD2 belongs to the NLR family and this protein is essential to control inflammation of the intestinal mucosa in permanent contact with commensal bacteria [1, 2]. After binding to its peptidoglycan derived MDP ligand, NOD2 and RICK will interact strongly leading to TAK1 recruitment.…”
Section: Introductionmentioning
confidence: 99%